2013
DOI: 10.1111/echo.12251
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Electromechanical Delay Measured by Tissue Doppler Imaging in Patients with Secundum Atrial Septal Defects

Abstract: SEE ARTICLES ON PAGES 699 AND 706Atrial septal defects (ASDs) cause left-to-right shunt because the pressure in the left atrium is usually higher than the right atrial pressure. Left-to-right shunting across the ASD produces dilatation and hypertrophy of the right atrium and right ventricle. The resulting increased pulmonary venous return causes left atrial dilatation. Enlarged atria may increase conduction time of the impulse originating in the sinus node as well as result in nonhomogeneous spread of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Atrial electromechanical delay duration is the sum of impulse propagation from sinus node to the atria and atrial electromechanical coupling duration. It has been studied in some clinical conditions . Deniz et al., in a study comparing tissue Doppler echocardiography and electrophysiological study, found a moderate correlation between ILCT‐echo and ILCT‐eps, and demonstrated that tissue Doppler echocardiography can be used for the measurement of interatrial and intra‐left atrial conduction times.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial electromechanical delay duration is the sum of impulse propagation from sinus node to the atria and atrial electromechanical coupling duration. It has been studied in some clinical conditions . Deniz et al., in a study comparing tissue Doppler echocardiography and electrophysiological study, found a moderate correlation between ILCT‐echo and ILCT‐eps, and demonstrated that tissue Doppler echocardiography can be used for the measurement of interatrial and intra‐left atrial conduction times.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that prolonged intra-and inter-atrial conduction times and inhomogeneous propagation of sinus impulses would be the characteristics of increased AF risk in various clinical conditions during sinus rhythm. 27 It has been studied in some clinical conditions, [28][29][30][31] and it was found that AEMD is significantly correlated with the prolonged maximum P-wave duration, P-wave dispersion, and degree of histopathological changes. [32][33][34] Previous studies evaluated the predictive role of intra-left atrial electromechanical delay for paroxysmal atrial fibrillation recurrence after cardioversion, [35][36][37] lone atrial fibrillation attack, 38 new-onset AF after acute myocardial infarction, 39 occurrence of atrial arrhythmias in adult patients with congenital heart diseases, 40 myotonic dystrophy type 1, 41 and atrial septal aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…A number of editorials addressing echo-Doppler related subjects were contributed by the author [17][18][19][20][21]; most of these are prepared at the request of the respective chief editors. These Based on these data, it was concluded that the long-term results of BPV are excellent and that BPV is the management of option in the treatment of valvar PS; however, our study raises concern regarding development of PI at long-term follow-up [16].…”
Section: Editorialsmentioning
confidence: 99%
“…A number of editorials addressing echo-Doppler related subjects were contributed by the author [17][18][19][20][21]; most of these are prepared at the request of the respective chief editors. These…”
Section: Editorialsmentioning
confidence: 99%
See 1 more Smart Citation